Regulating Na content and Mn defects in birnessite for high-voltage aqueous sodium-ion batteries - Xiaohui Zhu; Jing Xu; Qinghua Zhang; Tao Shen; Yuhang Zhuang; Tingting Chen; Shuang Li; Lin Gu; Hui Xia (Nature Communications)
Abstract Na-birnessite is a promising low-cost positive electrode material for aqueous sodium-ion batteries. However, its sodium storage capability is limited by narrow potential window and low redox activity in aqueous electrolytes. Herein, a Na-rich birnessite (NaMnO2•0.1H2O) with a highly ordered layered structure is reported as an advanced positive electrode for aqueous sodium-ion batteries, greatly suppressing Mn migration and its accompanying domino degradation effect, which enables a promoted upper charging cut-off potential up to 1.4 V (vs. Ag/AgCl), an enhanced specific capacity of 199.9 mAh g−1 at a specific current of 0.2 A g− 1 based on the mass of active material for positive electrode, and greatly improved structural stability. In particular, a 3.0 V Na x H2–x Ti2O5||NaMnO2•0.1H2O aqueous full cell prototype is validated, exhibiting a large specific energy of 117.1 Wh kg− 1 based on the total mass of active materials in both positive and negative electrodes as well as a long cycle life. This work elucidates how interlayer chemistry and structural defects influence sodium ion storage in layered structures and provides opportunities for developing high-voltage aqueous batteries with large specific energy.